The Role of HRIS Technology in Human Resource Management Efficiency in Higher Education - Dede Jaelani (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
In the era of digital transformation, efficient human resource (HRM) management has become a critical requirement for every organization, including universities. This study aims to analyze the role of the Human Resource Information System (HRIS) in improving HR management efficiency at several universities in Bandung. The research method used was qualitative with a descriptive approach, through interviews and observations of universities that have implemented HRIS. The results show that HRIS implementation has a significant impact on improving operational efficiency and HR governance. HRIS facilitates centralized employee data integration, automates administrative processes, and provides analytical data for strategic decision-making. Furthermore, this system also supports more targeted employee competency and career development and strengthens higher education institutions' digital transformation efforts. Thus, HRIS plays a crucial role not only in improving HR management efficiency but also in realizing modern, transparent, and highly competitive higher education governance.